Effects of a silane coupling agent on the tensile adhesive strength between resin and titanium. Issue 5 (15th February 2013) - Kato, Takahiro; Kimura, Hiroaki; Saigo, Kazuhiko; Yamada, Bunichiro; Yamauchi, Jyunichi; Anraku, Teruo
Abstract Adhesion of a cured dental opaquer, which masks metallic appearance and color, to sandblasted Ti aided by 3‐methacryloyloxypropyltrimethoxysilane (MPTS) is investigated. The tensile bond strengths of Ti and the opaquer are 43.3 and 45.9 MPa, respectively, when MPTS dissolved in ethanol (6 wt %) and premixed with the opaquer (3 wt %) are applied to the sandblasted Ti surface. Mirror finishing alone and sandblasting alone result in the bond strengths of 1.8 and 21.3 MPa, respectively. After thermal cycling (4 and 60°C for 5000 cycles), the bond strengths of the Ti with sandblasting and the MPTS treatment remain higher than that of the Ti with sandblasting only. Sandblasting and the MPTS treatment effectively promote the adhesion of the opaquer to Ti that rapidly forms an oxide surface layer. The silane‐aided adhesion of the opaquer to the sandblasted NiCr, CoCr, and AuAgPd alloys attain adhesive strengths of 33.2, 31.9, and 31.6 MPa, respectively. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013